ERRORS ON DIRECT AND INDIRECT QUOTATIONS IN THESIS WRITTEN BY STUDENTS OF ENGLISH LANGUAGE EDUCATION STUDY PROGRAM OF STKIP NIAS SELATAN IN 2020 - Manaraja, Joice Catherine (Universitas Nias Raya, 2023)
Writing is one of important skills in English, including academic writing. In academic writings consist of quotation. However, there are still many Students English Education Study Program of STKIP Nias selatan in 2020 made errors on direct and indirect quotations in thesis written.The aim of this study is to find the students’ errors on direct and indirect quotation and to know how errors occur in thesis written by Students ofEnglish. It was conducted by employing qualitative descriptive research. The students’ writing in 2020 of English Language Education Study Program was the subject of this research. Documentation was conducted as the technique in collecting data by students’ writing. The result of data analysis showed that they have errors in direct quotations, 1) tense, 2) punctuation commas, 3) reporting verb, 4) capitalization, 5) quotation within quotation, 6) quotation of 40 words or more, 7) punctuation period, 8) punctuation brackets while the errors in indirect quotation, 1) reporting verb, 2)single quotation, 3) punctuation commas, 4)tense, 5)capitalization, 6) punctuation period. Based on the finding, it is concluded that students made errors on direct and indirect quotation are 61 errors which is errors on direct were 34 errors and indirect quotations were 27 errors It is suggested to the educator who will write writing to know about rules of direct and indirect quotation. It is also suggested to students to learn more and practice how to using direct and indirect quotation in writing.